THE TRENDS OF SOCIAL MARKETING DEVELOPMENT IN KAZAKHSTAN (ҚазҰУ хабаршысы. Экономика сериясы, 2019)
Whilst social marketing has been continuing to capture increasing research attention indifferent settings across the globe, local movements and organizations in Kazakhstan are getting moreinvolved in social marketing activities as well. The research objective of the current study is to explorethe trends and challenges of social marketing in Kazakhstan. The study uses qualitative depth interviewmethod. Combined mixed purposeful sampling approach was employed with maximum variation samplingtechnique used to select the participants. The phenomenological research was used to analyzequalitative data to generate meaning units and develop descriptions. The analysis of the sixteen interviewswith experts revealed the major trends and challenges representing the current state of socialmarketing in Kazakhstan. The key findings of this study include the following: social marketing is growingand developing in Kazakhstan; the challenges facing social marketing in Kazakhstan include generalmisconceptions about marketing and social marketing, lack of funding and marketing expertise, andweak governmental support and regulation.